2013
DOI: 10.1002/chem.201302485
|View full text |Cite
|
Sign up to set email alerts
|

Atom‐Efficient Gold(I)‐Chloride‐Catalyzed Synthesis of α‐Sulfenylated Carbonyl Compounds from Propargylic Alcohols and Aryl Thiols: Substrate Scope and Experimental and Theoretical Mechanistic Investigation

Abstract: Gold(I)-chloride-catalyzed synthesis of α-sulfenylated carbonyl compounds from propargylic alcohols and aryl thiols showed a wide substrate scope with respect to both propargylic alcohols and aryl thiols. Primary and secondary aromatic propargylic alcohols generated α-sulfenylated aldehydes and ketones in 60–97 % yield. Secondary aliphatic propargylic alcohols generated α-sulfenylated ketones in yields of 47–71 %. Different gold sources and ligand effects were studied, and it was shown that gold(I) chloride ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 111 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…Before it had been shown that other metal catalysts, such as rhenium(I), bismuth(III) or iron(III) promote direct substitution of the hydroxyl group to generate the corresponding propargylic thioether [49] . After optimization of the reaction conditions a range of α‐sulfenylated aldehydes and ketones could be obtained in 47–97 % yield (Scheme 17a) [48b] . Experimental and DFT (density functional theory) studies showed that the reaction proceeds in two steps.…”
Section: Methods For the Synthesis Of α‐Sulfenylated Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before it had been shown that other metal catalysts, such as rhenium(I), bismuth(III) or iron(III) promote direct substitution of the hydroxyl group to generate the corresponding propargylic thioether [49] . After optimization of the reaction conditions a range of α‐sulfenylated aldehydes and ketones could be obtained in 47–97 % yield (Scheme 17a) [48b] . Experimental and DFT (density functional theory) studies showed that the reaction proceeds in two steps.…”
Section: Methods For the Synthesis Of α‐Sulfenylated Carbonyl Compoundsmentioning
confidence: 99%
“…Experimental and DFT (density functional theory) studies showed that the reaction proceeds in two steps. First, regioselective thiolation of the propargylic alcohol forms a sulfenylated allylic alcohol, which isomerizes to the desired α‐sulfenylated ketones [48b] . The methodology allowed the preparation of a wide range of ketones in a mild and efficient way.…”
Section: Methods For the Synthesis Of α‐Sulfenylated Carbonyl Compoundsmentioning
confidence: 99%
“…AuCl alone was found to catalyze both steps of the sequence as well; however, in this case, good selectivity was achieved only for interaction of aromatic thiols with internal alkynes . Thorough experimental and theoretical mechanistic investigations have been performed to shed light on Au‐catalyzed reaction sequence …”
Section: Formation Of Monofunctionalized Akenes (Vinyl Chalcogenides)mentioning
confidence: 99%
“…[17] Thorough experimental and theoreticalm echanistic investigations have been performed to shed light on Au-catalyzed reactionsequence. [18] Ni complexes were found to be very promising in ZÀH( Z =S, Se) bond addition to alkynes to obtain Markovnikov-type products. In the first report on Ni catalysis, it was shown that Ni(PPh 2 Me) 4 allowed to perform additiono fP hSH to 1-octyne under very mild reactionc onditions leading to ah igh yield (92 %) and excellent selectivity (> 91 %) of the branched product in as hort time (3 hv ersus 16-20 hi nt he case of Pd).…”
Section: Catalytic Systems Leadingt Om Arkovnikov-type (Branched)vinymentioning
confidence: 99%
“…In an additional study, the substrate scope was widely investigated, and detailed experiments on the reaction mechanism were performed. 46 The transformation most likely proceeded by sequential gold-catalyzed regioselective hydrothiolation followed by isomerization via a 1,2-hydride migration to generate the desired products.…”
Section: Hydrothiolation Rearrangementsmentioning
confidence: 99%